Role of Industries in Eco-development through Afforestation- a Case of Dadra & nagar Haveli - Pathan, R. S. (Indian Forester, 1998)
In tribal dominant and poverty stricken Union Territory of Dadra&Nagar Haveli , various incentives have brought in large scale industrialisation. The goods manufactured have no relevance to local resources and the local market. An industrial culture has come face to face with the tribal culture. Having arrived , the industries have bigger role to play in ecological development , the very base for the people of the region. The programme has to go beyond the ceremonial planting of trees by industry. A location specific voluntary contribution from industry is vital for reciprocal growth.